EKSISTENSI PERUSAHAAN SEBAGAI ORGAN MASYARAKAT - Tri Handayani (Universitas Wahid Hasyim, 2008)
Almost in all economic sector had negative growth in1998 but the existenci of company as social organ always has a role to encourage a desire of worl bussines the existenci of company as social organ will always be dynamic head for the growth social culture, cause in the middle of society the company always become the centre of economic actifity.Key words: The existence of company, social organ